AI utilization training in creating interactive learning media for teachers - Masharyono Masharyono; Agus Rahayu; Syamsul Hadi Senen; Ratih Hurriyati (Jurnal Abmas, 2026)
Most teachers do not yet have direct experience using Artificial Intelligence (AI) in the classroom. This workshop aims to provide teachers with knowledge and practical skills for using AI to create interactive, innovative learning materials. This training focuses on using AI to create more creative learning materials in response to the challenges of digital transformation in education in Kepulauan Seribu. The training methods include presenting materials, demonstrating the use of various AI platforms, and hands-on practice in designing AI-based learning materials. Through this training, teachers gain new insights into AI's potential as an effective, efficient, and engaging learning tool. Evaluation results indicate that a small portion of participants were already familiar with and using AI technology, but the majority of teachers had not yet optimized its use in classroom learning. This community service activity can enhance teachers’ digital competencies and encourage the creation of creative, inspiring, and student-centered learning media in the digital age, thereby positively impacting the quality of the teaching and learning process.   Abstrak Sebagian besar guru belum memiliki pengalaman langsung dalam menggunakan Artificial Intelligence (AI) dalam pembelajaran. Kegiatan ini bertujuan untuk memberikan pengetahuan serta keterampilan praktis kepada para guru terkait pemanfaatan AI dalam pembuatan media pembelajaran yang interaktif dan inovatif. Pelatihan ini mengangkat tema pemanfaatan ai untuk mewujudkan media pembelajaran yang lebih kreatif sebagai respons terhadap tantangan transformasi digital di bidang pendidikan di Kepulauan Seribu. Metode pelaksanaan kegiatan meliputi penyampaian materi, demonstrasi penggunaan berbagai platform AI, serta praktik langsung dalam merancang media pembelajaran berbasis AI. Melalui pelatihan ini, para guru memperoleh wawasan baru mengenai potensi AI sebagai alat bantu pembelajaran yang efektif, efisien, dan menarik. Hasil evaluasi menunjukkan bahwa sebagian kecil peserta telah mengenal dan memanfaatkan teknologi AI, namun mayoritas guru belum mengoptimalkannya dalam proses pembelajaran di kelas. Kegiatan pengabdian kepada masyarakat ini dapat meningkatkan kompetensi digital guru serta mendorong terciptanya media pembelajaran yang kreatif, inspiratif, dan sesuai dengan kebutuhan murid di era digital, sehingga berdampak positif pada peningkatan kualitas proses belajar-mengajar. Kata Kunci: artificial intelligence; kompetensi guru; media pembelajaran; pengabdian kepada masyarakat